The Responsibility of Intellectuals Reflections by Noam Chomsky and others after 50 years - Allott, Nicholas; Knight, Chris; Smith, Neil; Chomsky, Noam (UCL Press, 2019)
With the publication of 'The Responsibility of Intellectuals' half a century ago, Noam Chomsky burst onto the US political scene as a leading critic of the war in Vietnam. Privilege, he argues, brings with it the responsibility to tell the truth and expose lies, but our intellectual culture only pays lip-service to this ideal. The essay has been described as 'the single most influential piece of anti-war literature' of the Vietnam War period. Since then, Chomsky has continued to equip a growing international audience with the facts and arguments needed to understand - and change - our world. According to The New York Times, Chomsky 'may be the most widely read American voice on foreign policy on the planet today'. This book revisits 'The Responsibility of Intellectuals' half a century on. It includes six new essays written to celebrate Chomsky's famous intervention and explore its relevance in today's world. Nicholas Allott, Chris Knight, Milan Rai and Neil Smith have studied and written about Chomsky's thought for many years, while Craig Murray and Jackie Walker describe the personal price they have paid for speaking out. The book finishes with Chomsky's recollections of the background to the original publication of his essay, followed by extensive commentary from him on its 50th anniversary.